Colonic malignant melanoma, primary or metastatic? Case report - Gürdeniz SERİN and Başak DOĞANAVŞARGİL and Cemil ÇALIŞKAN and Taner AKALIN and Murat SEZAK and Müge TUNÇYÜREK (Turkish Journal of Gastroenterology, 2019)
-